Mortalidad evitable, Medellín 2004 a 2009 (2013)
ABSTRACT: To determine the structure of avoidable mortality and Years of Potential Life Lost (ypll) in Medellín in the period 2004-2009). Methodology: in a descriptive study using data from the dane, the inventory of Causes of Avoidable Mortality (icme) proposed by Gómez in 2006 was used. The median rates of avoidable mortality adjusted for age, sex and year were calculated, and the population of Medellin between 2004 and 2009 was used as denominator. The ypll were calculated for each cause of Avoidable death by summing the difference between the life expectancy of Colombia in 2009 and the age of death. These ypll were adjusted using the direct method and the standard population of Colombia. Results: in the six years of the study, 48.9% of the deaths (35,046) were considered avoidable. Deaths related to mixed measures were predominant (875.1 per hundred thousand inhabitants); these deaths were higher for men, and the median age was 36 years old or younger in 50% of the cases. In this group, violent causes accounted for 58% of the deaths, showing a ratio of 7:1 in favor of men. In 2009, the amount of ypll increased in 22.9% compared to the previous year. Conclusion: in this study, a positive gradient of avoidable mortality was observed, that is to say, the value of the avoidable mortality indicator is higher for more recent years. Similarly, the rates of avoidable mortality were higher for men than for women during the studied period, both for each year and in general.